LOIALIZAREA / FIDELIZAREA UTILIZATORILOR - KULIKOVSKI, Conferențiar universitar , Lidia (BIBLIOPOLIS, 2020)
The library evolution is not based only on the classic, traditional idea. In modern world there is no difference between cafe, bar, theater, museum, cinema, disco, karaoke and library. Each of these institutions should attract their users/clients/public, serve them and gain their fidelity by providing quality, excellent services. The author try to provide a theoretical and praxiological framework, tacts, tips, ideas for users loyalty. The patterns of users and library behavior are constant, and will change in case of revision of librarians’ conscience towards the users, towards the library and the activity – the essence of the activity. In the future we will learn how to identify and to provide the best solutions to regain the confidence and goodwill of each user that is the direct way to loyalty.